Paleomagnetic investigation of some Slovak Quaternary travertines - TÚNYI, Igor; KÖHLER, Eduard (Contributions to Geophysics and Geodesy, 2021)
Present publication is the first attempt to use Slovak fresh-water limestones for paleomagnetic investigation. Samples were collected from six well-known Slovak localities. The small values of rotation of the main paleomagnetic direction, from the present direction of geomagnetic field, confirm the tectonical stability of Slovak territory during the Quaternary. Paleomagnetic methods are capable to contribute in the future to the precision of Quaternary stratigraphy of Slovakia.